PLACENTA ACCRETA SPECTRUM DISORDER IN THE FIRST SEMESTER: A SYSTEMATIC REVIEW - Laurenso Lomi, Eldwin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Placenta accreta is one of the deadliest obstetric placental implantation anomalies that can result in severe bleeding, shock, uterine perforation, secondary infection, and even death. It is considered to be one of the most serious placental anomalies. It was demonstrated that higher blood levels of PIGF remained to be strongly and positively related with placenta accreta. Furthermore, a history of a previous cesarean section, as well as smoking, were found to be substantially associated with placenta accreta in a positive way. PIGF has been identified as a marker for placental trophoblasts in studies. Furthermore, having a low PIGF level was connected with an increased risk of developing preeclampsia, pregnancy loss, early delivery, and low birth weight. These pregnancy problems and placenta accreta are all symptoms of underlying diseases that impair placental development. The placenta accreta begins to form during the first trimester of pregnancy. PAPP-A levels in the blood were found to be significantly and favorably associated with placenta accreta. Previous study as well as the current investigation have demonstrated that the levels of placental markers in maternal serum may fluctuate in pregnant women who either have or are destined to acquire placental accreta. Markers identified in maternal serum during the first trimester may aid in the prenatal diagnosis of placenta accreta. Furthermore, being aware of the potential risks at an early stage may assist to better explain the findings of an MRI or ultrasonography.